3D printed planetary gearbox for robotic arm joints - Hrdlička, Filip (Design of Machines and Structures, 2022)
3D printing technology has become very popular in last several years as a cheap way how to make different parts. 3D printing is as a perfect tool for prototyping of various, mostly difficult, structures which is the reason why it is more and more use in mechanical design. This article is focused on assessment if 3D printing technology can be used for creating light, durable and cheap variation of classic metal or moulded plastic gearboxes for electric motors which can be used for low cost robotic arms. For this purpose was in CAD software designed a small two-stage planetary gearbox with identical stages. All parts of gearbox were printed by FDM 3D printer with most common printing material PLA. The gearbox has been tested on noise, durability, resistance and maximum load on lever to find out where can be potential of 3D printed gearboxes.